Studies of polymer-stabilized bimetallic nanoclusters and synthesis of substrate peptides for electronic chemical biosensors - Ren, Zhaoyang (Kansas State University, 2023)
Two research projects were conducted and they consist of catalytic oxidation of C-H bond utilizing bimetallic nanoclusters and synthesis of substrate peptides for electronic chemical detection of overexpressed proteases in breast cancers. First, inactivated C(sp³)-H bonds have strong bond dissociation energy of ~105 kcal/mol, and it is a challenge to find a way to functionalize C(sp³)-H and provide regioselective and stereo-selective functionalization. Bimetallic nanoclusters have unique catalytic activity along with chiral polymeric stabilizers may achieve such objectives. Therefore, a series of chiral polymers, such as chiral-substituted polyvinylpyrrolidones (CSPVP), were designed and synthesized for the stabilization and support of the bimetallic nanocluster metals, which may provide unique oxidative activity and chiral selectivity in various organic transformation reactions. The designed polymers and their corresponding stabilized bimetallic nanoclusters Cu/Au and Pd/Au were synthesized, and characterized, and various catalytic oxidation reactions utilizing the nanoclusters were carried out. Results indicated that bimetallic nanoclusters show higher reactivity than monometallic nano clusters and regio- and stereo- selectivities were also observed in the catalytic oxidation reactions. In the second project, a series of polypeptides were designed, synthesized and attached to a ferrocene moiety in one end and a H₂N-(CH₂)₄CO linker in the opposite end. They were used to profile overexpressed proteases in breast cancers using electrochemical technique. Proteases MMP-9 and cathepsin B were investigated, since they are overexpressed in breast cancers, particularly triple-negative breast cancer (TNBC). The quantification and profiling of proteolysis rates of a group of overexpressed proteases will provide a patent of proteolytic activity. This in turn may allow the recognition of the presence and progression of a specific cancer such as TNBC.
Keywords: Bimetallic nanoclusters; Polymer; Peptide